2002
DOI: 10.1210/jcem.87.4.8429
|View full text |Cite
|
Sign up to set email alerts
|

Human Growth Hormone Replacement in Adult Hypopituitary Patients: Long-Term Effects on Body Composition and Lipid Status—3-Year Results from the HypoCCS Database

Abstract: The Hypopituitary Control and Complications Study is an international surveillance study evaluating efficacy and safety of GH therapy of adult GH-deficient patients in clinical practice. The present report examined baseline data from 1,123 adult onset (AO) and 362 childhood onset (CO) patients, as well as efficacy in 242 patients who had completed 3 yr of GH treatment. At study entry, mean height, body mass index, waist to hip ratio, and lean body mass were significantly (P < 0.001 for each) lower in CO compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
47
3
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 19 publications
15
47
3
2
Order By: Relevance
“…In this analysis, both men and women in each age category demonstrated an improvement in WHR with 1 year GH replacement (36). An analysis of different aged patients enrolled in HypoCCS confirmed this finding, with older GHD patients (O60 years old) having a more pronounced decrease in WHR after 3 years GH treatment than younger patients, despite having no significant improvement in LBM (37). …”
Section: Clinical Characteristics Of the Hypopituitary Gh Deficient supporting
confidence: 59%
See 1 more Smart Citation
“…In this analysis, both men and women in each age category demonstrated an improvement in WHR with 1 year GH replacement (36). An analysis of different aged patients enrolled in HypoCCS confirmed this finding, with older GHD patients (O60 years old) having a more pronounced decrease in WHR after 3 years GH treatment than younger patients, despite having no significant improvement in LBM (37). …”
Section: Clinical Characteristics Of the Hypopituitary Gh Deficient supporting
confidence: 59%
“…2). Attanasio et al reviewed results from 242 HypoCCS patients and reported the greatest improvement in LDL/HDL ratio in patients aged 40-60 years when compared with both younger and older patients (37).…”
Section: Lipidsmentioning
confidence: 99%
“…Thus, with prolonged GH treatment with a physiological replacement dose there is a trend for trunk FM values to normalize, which translates into a clinically relevant reduction of predicted cardiovascular risk. This is further supported by the changes in total and LDLcholesterol, which were consistent with long-term data in Caucasian patients [20].…”
Section: Discussionsupporting
confidence: 88%
“…The 48-week safety profile was consistent with published data [16,20,22,23] and available clinic experience in Caucasians and Japanese patients. There were two patients who developed signs of glucose intolerance under GH replacement; one of these was able to continue treatment after adequate dose reduction, but the second, with a borderline high BMI value for Japanese, had to discontinue.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation